Voluntary Exercise-Induced Activation of Thyroid Axis and Reduction of White Fat Depots Is Attenuated by Chronic Stress in a Sex Dimorphic Pattern in Adult Rats - Parra-Montes de Oca, Marco Antonio; Gutiérrez-Mariscal, Mariana; Salmerón-Jiménez, Ma Félix; Jaimes-Hoy, Lorraine; Charli, Jean-Louis; Joseph-Bravo, Patricia (Frontiers in Endocrinology, 2019)
The activity of the hypothalamus-pituitary-thyroid (HPT) axis is inhibited by energy deficit, by acute or chronic stress, but activated by cold exposure or exercise. Because stress curtails acute cold induced activation of HPT, we evaluated the effect of chronic stress on HPT axis response to voluntary exercise, a persistent energy-demanding situation. Adult male and female Wistar rats were exposed to restraint stress, 30 min/day for two weeks, or to isolation (Iso) (postnatal day [PND] 30-63). Exercise was performed (7PM-7AM) in a running wheel, sedentary controls stayed in individual cages (Sed); at 7AM they were housed with their cage mate or individually (Iso); food intake by the exercised group was measured day and night to pair-fed Sed. At sacrifice, hormones, mRNA levels and tissue weights were quantified. Control or restrained adult rats had access to running wheel daily for two weeks. Compared to C, exercise decreased white adipose tissue (WAT) mass in females and males, increased PVN-Trh expression in males proportionally to exercise performed, and increased TSH and T4 serum concentration in females. These changes were not detected in restrained groups. Starting at PND 63 control (2/cage) and isolated (1/cage) rats either exercised on 10 alternated nights or were sedentary. In control male animals, compared to Sed rats, exercise did not decrease WAT mass, nor changed HPT axis activity, but increased Pomc and deiodinase 2 (Dio2) expression in mediobasal hypothalamus (MBH), adrenergic receptor 3 (Adrb3) and UCP-1 in brown adipose tissue. In control female animals, exercise decreased WAT mass, increased Pomc, Dio2 and Trhde expression in MBH, and TSH serum concentration. Iso females had lower TSH and T4 serum concentration, Dio2 and Trhde expression in MBH than controls. The stress response was higher in isolated males than females, but in males it did not alter the effects of exercise, in contrast to isolated females that had a blunted response to exercise compared to controls. In conclusion, chronic stress interferes with metabolic effects produced by exercise, such as loss of WAT mass, coincident with dampening of HPT activity.